Modelling of job satisfaction in literature from 2019 to 2021 - Cruz García Lirios (International Journal of Public Administration Studies, 2022)
The organizational process that goes from the knowledge networks to the strategic alliances supposes a management, production and transfer of information that the literature differentiates according to the degree of empathy, commitment, entrepreneurship, innovation and satisfaction of leaders and followers. In this sense, the objective of this study was to study the phenomenon in coffee growers in central Mexico. From a structural model, after establishing the reliability and validity of an instrument, it was found that innovation determines satisfaction, although the type of study, sample selection and analysis limit the findings to the specific context of the investigation. Lines concerning the extension of work to different contexts and samples are noticed.